FEASIBILITY OF SALTED FISH ON SUMBER JAYA KAMPUNG MELAYU DISTRIK IN BENGKULU CITY - Reswita Reswita (BPFP Faperta UNIB, 2014)
The aims the research was to analysis feasibility of salted fish on Kampung Melayu distrik in Bengkulu City. The responden in the research was 20 processor salted fish. Analisys method is income analysis, R/C ratio, and ROI (Return of Investment). The result showed that Income from salted fish is Rp. 134.457,15, R/C ratio is 1,2, and ROI 9,7%. From the research can be concluded that the salted fish business was feasible to carry on based on.